Precalculus: Concepts Through Functions, A Unit Circle Approach to Trigonometry (3rd Edition)

Published by Pearson
ISBN 10: 0-32193-104-1
ISBN 13: 978-0-32193-104-7

Chapter 11 - Sequences; Induction; the Binomial Theorem - Section 11.1 Sequences - 11.1 Assess Your Understanding - Page 828: 75



Work Step by Step

Recall the formulas: $\displaystyle \sum_{k=1}^{n} k^2=1^1+2^2+...+n=\dfrac{n(n+1) (2n+1)}{6}$ and $ \sum_{k=1}^{n} c=c+c+c+...+c=cn$ We rewrite the given sequence and apply the above formulas: $\displaystyle \sum_{k=1}^{16} (k^2+4) = \sum_{k=1}^{16} (k^2) + \sum_{k=1}^{16} (4)=\dfrac{16(16+1) [(2)(16)+1)]}{6}-(16)(4) \\=1496+63 \\= 1560$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.